Vertebrate Succession in the Ischigualasto Formation - Martínez, Ricardo N. (2013)
The Upper Triassic (Carnian-Norian) Ischigualasto Formation has yielded a diverse vertebrate fauna that records the initial phase of the evolution of dinosaurs. Radioisotopic dates from ash layers within the formation provide a chronostratigraphic framework, and stratigraphic and sedimetological studies have subdivided the formation into four members and three abundance-based biozones. We describe two new basal dinosauromorphs, an unnamed lagerpetid, and a new silesaurid, Ignotosaurus fragilis gen. et sp. nov., which increase to 29 the number of vertebrates in the Ischigualasto fauna. We provide a census of 848 fossil specimens representing 26 vertebrate taxa logged to stratigraphic intervals of 50 m. This temporally-calibrated census shows that abundance and taxonomic diversity within the Ischigualasto Formation does not change suddenly but rather appears to gradually decline in response to climatic deterioration. The only abrupt shift in faunal composition occurs at the end of the second of three biozones, when the abundant cynodont Exaeretodon is replaced by the rare dicynodont Jachaleria.